LESSON OBSERVATION STAGE (PRE-OBSERVATION, WHILE-OBSERVATION, POST-OBSERVATION) - Shamsuddinova Diyora Yorqinbekovna (Journals Park Publishing, 2023)
Classroom observations in school are an important tool for gaining an overview of patterns and trends, capturing the difference between what is said and what is actually done. It can form a good basis for continued development and improvement work. Research shows that there is a clear connection between the development and further training of teachers’ professions and students’ learning. You can use the initial meeting to introduce yourself to these people and to explain to them the purpose of your observation. In the context of this discussion, you can find out what their expectations are, and you should also help them to understand what your needs are. The school might have hosted teachers such as you in the past, so they might have some pre-conceptions about what your role is; or you might be their first visitor. Either way, it is important to go over these details, to ensure that there are no misunderstandings.
Keywords: fundamentally, monitoring, traditional, technology, learning, teaching, development, difference, example.